Influence of a delamination on Lamb wave excitation by a nearby piezoelectric transducer. (February 2021) - Shpak, Alisa N; Golub, Mikhail V; Mueller, Inka; Eremin, Artem; Kathol, Jens; Fritzen, Claus-Peter
This article presents the results of theoretical and experimental investigations of characteristic changes of Lamb wave excitation and scattering by a strip-like horizontal delamination in a layered elastic waveguide for Lamb waves induced by a piezoelectric wafer active sensor. The boundary integral equation method is used to describe wave propagation in an infinite layered waveguide with a delamination, while the frequency domain spectral element method is employed to model the dynamic behaviour of the piezoelectric wafer active sensor, which allows to simulate debonding between the piezoelectric wafer active sensor and the waveguide. Experimental investigations of the dynamic interaction of the piezoelectric wafer active sensor with a layered plate containing a horizontal delamination is conducted for several damage scenarios, showing a good agreement with the results obtained using the developed mathematical model. The obtained mathematical model is employed to analyse alteration of the piezo-induced Lamb waves including modes' decomposition due to delamination. The conversion and/or conservation of the Lamb waves on account of a delamination is investigated. The electro-mechanical impedance of the piezoelectric transducer and the stress intensity factors of a delamination are analysed in dependence on the delamination location.